2019-20 influenza coverage among healthcare workers: how a Northern-Italian Region tackles hesitancy. (30th September 2020) - Antinolfi, F; Brunelli, L; Malacarne, F; Bucci, F G; Varadi, G; Gallo, T; Cocconi, R; Brusaferro, S
Abstract: Introduction: WHO stresses the need to implement multi-component interventions to raise coverage among healthcare workers (HCWs). We investigated different HCWs influenza immunization programs within Friuli Venezia Giulia (FVG) Region hospitals (Italy) during 2019-20 flu season with the aim of identifying the most effective strategies to tackle hesitancy. Methods: In December 2019 we collected from FVG hospitals: number of employed HCWs, vaccination strategies against flu and refusers management during 2019-20 flu season. We obtained data about HCWs flu vaccination coverage from the regional database; Chi-square test was used to find correlation between strategies and coverage. Results: We collected data from 7/7 hospitals for a total of employed HCWs of 12, 557 (average 1, 794; range 467-3, 922); 2 hospitals being academic centers and 2 research institutions. All hospitals promoted flu vaccination using emails, notice on hospital website and posters display; 3/7 organized training courses. Vaccination was always provided within the hospital in a dedicated easy and free access room; most hospitals (5/7) also offered ward on-site sessions, some allowing ward self-administration (3/7) or organizing on demand extra-sessions (2/7). No countermeasures were taken in case of refusal. Regional HCWs flu vaccination coverage resulted to be 24.9% (range 17-33.3). Multi-component intervention including passive and active offer, communication and education activities was confirmed to be significantly associated with higher HCWs flu coverage (OR 1.7; CI 1.6-1.9; p < 0.01), as well as being the hospital an academic center or a research institution (OR 1.3; CI 1.2-1.5; p < 0.01). Conclusions: Different strategies to foster HCWs vaccination were adopted in FVG Region during 2019-20 flu season. The multi-component approach producing the best results should be further analyzed in order to identify the most effective recipe to be shared both nationally and internationally. Key messages: Investigating the relation between HCWs flu immunization strategies and their effect is crucial to identify best practices. A multi-component approach including passive and active offer, communication and education activities seems the most effective way to tackle influenza vaccine hesitancy among HCWs.